Urban spatial growth and geo-environmental risk in Pokhara Metropolitan City: A geospatial analysis - Poudel, Khagendra Raj; Shrestha, Shobha (Nepal Journal of Environmental Science, 2025)
Urban spatial growth is shaped and directed by geo-environmental and socio-economic factors. Understanding the relationship between geo-environmental risks and urban spatial growth is essential for safe and sustainable urban development. In this context, this study investigates the urban growth in the geo-environmentally fragile area of Pokhara Metropolitan City, Nepal, using GIS and remote sensing tools. Urban spatial growth was determined using aerial photos from 1978, and multisource remote sensing data collected from 1990 to 2020. A geologically fragile zone was traced from the 1998 Geological Map of Pokhara Valley and sinkhole occurrences were documented during field visits. Results indicate that the built-up area has expanded more than four times, from 1.70 km2 in 1978 to 8.83 km2 with a growth rate of 1.87% to 8.74% in 2020. The Ghachok formation indicates a heavy concentration of urban development in this fragile area, increasing hazards like subsidence or sinkholes. This study emphasizes that increased population pressures are causing increased vulnerability in the geo-environmentally fragile Ghachok Formation area which comprises 25,713 built-up structures and over 93,000 populations. The necessity of integrating geo-environmental risk into developmental policies and strategies is emphasized to minimize the consequences on environmental sustainability. The results of the study enhance the understanding of the relationship between urban growth and geo-environmental risk areas to help in the formulation of an effective plan of conservation, development, and reduction of hazard risks in vulnerable highly populated zones.